Study on Analysis of Extension Participation of National Horticulture Mission Beneficiaries in Davanagere District in India - J. Raghuraja; M. Madhumathi; S. Shashikumar; M. Sudheendra (New Visions in Science and Technology Vol. 5, 2021)
The present study was conducted in all the six blocks (taluks) of Davanagere district of Karnataka state, India with the objectives to understand the extension participation of National Horticulture Mission beneficiaries and to analyze the extent of participation of National Horticulture Mission beneficiaries in various extension programmes. The sample size was 144 randomly selected beneficiaries of National Horticulture Mission from 24 villages. Ex-post facto research design was employed for this study. The results revealed that family members (34.26 %), neighbors (33.56 %), friends and relatives (33.45) are the major sources of information for the NHM beneficiaries followed by other service providers, fellow beneficiaries and NHM personnel. Farm magazine (66.21 %), radio (57.87 %), news papers (55.10 %), internet source (44.44 %), WhatsApp (42.36 %) and mobile SMS (32.27 %). In case of contact with extension personnel, 42.82 per cent of beneficiaries had contact with agricultural assistant followed by 36.11 per cent with assistant agriculture officer, 30.09 per cent with veterinary officer and 28.70 per cent had contact with agriculture officer. The extension participation reveals that 33.45 per cent of beneficiaries participated in group meetings whereas, 33.10 per cent in krishi melas, 31.02 per cent in field visits and 28.47 per cent in training programmes. In all, 40.97 per cent of beneficiaries visited town or cities twice in a week while, 38.18 visited once in a week and 16.67 per cent visited once in fortnight.